(3GdbUjOI GdeaMeIs - (3eMeO Hf GdMSf Hf eMeO Hf YHO Gddg GdcdGYj GdMejQj GdjeGfjs ((3bQjI MhJ s)
(3ChdgG (B:s
(3Ndjdj gd QHY HoMaGJ ebaQ Pj GdLhi Ch ojNHQ s
(3BNQgG (B:s
(3hYfOj CeKGd dgG dG JZQfj hZjQj jYei Ohf PGc hjMUQ JeJ GdbUjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdbUjOI YOJgG KdGK eFI hGKfG YTQ HjJkGs
(3jLjH HgG GdaVd Hf JGQhM GdQhej hgj HJaSjQgGs
(3Hbde eged GdfbW CMjGfkGs
(3cGf GdeDda MjkG (B404(3g`` s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdCOHs